Economics and management of competitive strategy - Spulber, Daniel F. (World Scientific, 2009)
"This book provides a comprehensive and integrated approach to management strategy that is based on economics. A basic introductory strategy text that integrates economic analysis with management strategy, it takes into account global competition and high-tech (Internet) developments, and recognizes that companies today can no longer expect to sustain competitive advantage but must rely on innovation (of products, processes, and transactions). Although many of the principles are illustrated with numerical examples, the text does not require a background course in economics or mathematics, and does not contain technical graphs or equations. Thus, the book is suitable for undergraduate managerial economics and strategy courses, as well as for introductory MBA courses in business strategy and as a companion to case studies." -- Zadní s. obálky
Keywords: strategický management -- ekonomické aspekty; podnikový management -- ekonomické aspekty; podniková ekonomika; konkurenceschopnost; strategic planning -- economic aspects; industrial management -- economic aspects; managerial economics; competitiveness; učebnice vysokých škol; textbooks (higher)